2023
DOI: 10.1186/s12575-023-00198-y
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal microRNA-342-5p secreted from adipose-derived mesenchymal stem cells mitigates acute kidney injury in sepsis mice by inhibiting TLR9

Abstract: Background Sepsis-related acute kidney injury (AKI) is an inflammatory disease associated with extremely high mortality and health burden. This study explored the possibility of exosomes secreted by adipose-derived mesenchymal stem cells (AMSCs) serving as a carrier for microRNA (miR)-342-5p to alleviate sepsis-related AKI and investigated the possible mechanism. Methods Serum was obtained from 30 patients with sepsis-associated AKI and 30 healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Xing et al found that EXOs derived from MSCs exhibited protective effects on endothelial cells in an in vitro model of atherosclerosis, and this protective effect was mediated by the action of miR-342-5p, which targeted PPP1R12B [ 45 ]. Moreover, Liu and colleagues nicely proved that exosomal miR-342-5p derived from MSCs had the ability to mitigate acute kidney injury by inhibiting TLR9 in a sepsis mouse model [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Xing et al found that EXOs derived from MSCs exhibited protective effects on endothelial cells in an in vitro model of atherosclerosis, and this protective effect was mediated by the action of miR-342-5p, which targeted PPP1R12B [ 45 ]. Moreover, Liu and colleagues nicely proved that exosomal miR-342-5p derived from MSCs had the ability to mitigate acute kidney injury by inhibiting TLR9 in a sepsis mouse model [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al. conducted a study that showed miRNA-342-5p in exosomes secreted from AD-MSCs via TLR9 inhibition leads to the reduction of acute kidney damage (AKI) in LPS-induced sepsis mice ( Liu W. et al., 2023 ). This miRNA facilitates cellular autophagy by downregulating TLR9 expression, thereby leading to protection against sepsis-associated AKI.…”
Section: Exosomes-tlrs Intraction and Infection Controlmentioning
confidence: 99%
“…This miRNA facilitates cellular autophagy by downregulating TLR9 expression, thereby leading to protection against sepsis-associated AKI. The results suggest that by influencing necrosis, inflammation, and apoptosis, selective activation of renal proximal tubule TLR9 may worsen ischemic AKI ( Liu W. et al., 2023 ). In addition, Zhang et al.…”
Section: Exosomes-tlrs Intraction and Infection Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the therapeutic efficacy of EVs in sepsis was partially diminished when transfected with miR-21a-5p inhibitors ( Niu et al, 2023 ). Liu et al reported that miR-342-5p secreted by h-AMSC-derived EVs negatively regulated TLR9 to induce autophagy, thereby attenuating inflammation induced by LPS and improving acute kidney injury (AKI) in a mouse model ( Liu et al, 2023 ). hplMSC-EVs could ameliorate LPS-induced inflammation in RAW264.7 cells by regulating TLR4-mediated NF-κB/MAPK and PI3K signaling pathways ( Hu et al, 2022 ).…”
Section: Msc-derived Extracellular Vesicles Regulate or Are Regulated...mentioning
confidence: 99%